Optimal Sensor Treatment in a Survey of Micro-Electro Mechanical Systems for WSN Holes - Basha, M. John; Ambika, I.; S, Santhosh (Journal of Neonatal Surgery, 2025)
Area coverage in wireless sensor networks (WSN) is a non-trivial undertaking due to misunderstanding of the comparatively tiny sensor node (SN) required to protect a study area, as well as the restrictions of energy reserve, control, and communiqué ranges. A crucial factor in any WSN's successful functioning is WSN performance in terms of area-coverage optimization. The present state of WSN hole research is examined, as well as the relative benefits and downsides of the many solutions put out to address different kinds of holes. The distributed techniques presented in this paper allow nodes to cooperate autonomously and find coverage holes. Keywords—component, formatting, style, styling, insert Planning for research articles took into account node type, distribution method, data transfer and sensing range, comprehensive coverage tracking, and GPS methodology.